FORMATION OF THE REVOLUTIONARY MOVEMENT IN TURKEY AND THE EDUCATIONAL PROCESSES IMPLEMENTED BY THEM (American Journal of Research in Humanities and Social Sciences, 2023)
This article analyzes the social processes that led to the jadidism movement. Also, the main marifian views of the jadidist movement and the fundamental content and essence of the ideas they put forward are comparatively revealed. The importance of this article is highlighted by the main reasons for the actions of new-minded intellectuals among the people of Turkestan against colonial oppression.